Strategi Pentahelix Badan Nasional Penanggulangan Terorisme dalam Menurunkan Potensi Radikalisme di Indonesia - Dedi Kurnia; Mhd Halkis; David Yacobbus (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Radicalism in Indonesia, particularly when claiming to represent Islam, is driven by socio-historical, political, economic, social, and cultural factors that are exploited by terrorist groups to manipulate Muslims on a global scale. Such radicalism has led to various criminal acts that have shaken Indonesia, especially since the reform era, disrupting the safety and well-being of its people. The factors contributing to radicalism's emergence include a lack of accurate religious understanding, dogmatic interpretations, and strict religious prohibitions. Inadequate knowledge of history and sociology also plays a role. The government has taken steps in counterterrorism, including establishing the National Counterterrorism Agency (BNPT) and Densus 88 Anti-Terror. Legal and institutional measures are crucial in confronting terrorism threats. The "pentahelix" approach, involving the government, society, academia, media, and the business sector, is vital in creating a secure environment free from terrorism. Collaboration among relevant parties is essential in addressing the threat of radicalism in Indonesia, with hopes for harmonious cooperation. This research employs a literature review method, gathering data from academic journals, books, and peer-reviewed sources to gain a comprehensive understanding of the topic.